2009
DOI: 10.1111/j.1365-2915.2008.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

A carbon dioxide, heat and chemical lure trap for the bedbug, Cimex lectularius

Abstract: A trap for the collection of bedbugs, Cimex lectularius Linnaeus (Hemiptera: Cimicidae), is described. The trap was baited with CO2 (50-400 mL/min), heat (37.2-42.2 degrees C) and a chemical lure comprised of 33.0 microg proprionic acid, 0.33 microg butyric acid, 0.33 microg valeric acid, 100 microg octenol and 100 microg L-lactic acid, impregnated into a gel. Laboratory studies, conducted in a square arena measuring 183 cm on each side, showed that traps with and without baits captured adult bedbugs, but trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 22 publications
(34 reference statements)
1
79
0
9
Order By: Relevance
“…Recently, attraction to these cues was confirmed in trapping experiments (Anderson et al, 2009;Wang et al, 2009). In 1932, Rivnay observed that bed bugs were attracted to cold mouse and rabbit skins, and suggested that volatiles associated with these host skins are part of the mechanism regulating host seeking behaviour (Rivnay, 1932).…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…Recently, attraction to these cues was confirmed in trapping experiments (Anderson et al, 2009;Wang et al, 2009). In 1932, Rivnay observed that bed bugs were attracted to cold mouse and rabbit skins, and suggested that volatiles associated with these host skins are part of the mechanism regulating host seeking behaviour (Rivnay, 1932).…”
Section: Introductionmentioning
confidence: 73%
“…Moreover, behavioural experiments using different synthetic blends and concentrations of sulcatone and C 8 -C 10 aldehydes will be required to confirm the modification of local search observed with our human body extracts alone. In all, this might lead to the improvement of monitoring traps (Anderson et al, 2009;Wang et al, 2009). These results improve our knowledge about the chemical ecology of bed bugs and their relation to their human host.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…72,73 In addition to pheromones, semiochemicals include important chemical Many active bed bug monitors use compounds considered kairomones, such as carbon dioxide or other host odors that are components of human sweat or breath like proprionic acid, butyric acid, valeric acid, lactic acid, and octenol. 76 Carbon dioxide and heat have proven to be the two most effective attractants used for bed bug monitoring, 76,77 and human odor in the absence of carbon dioxide and heat seems to have a very weak influence on bed bug behavior. 78 Two active monitors, the CDC3000 (Stern Environmental Products, Secaucus, NJ) and the NightWatch (BioSensory, Inc., Putnam, CT), along with a homemade dry ice trap were evaluated for their ability to trap bed bugs.…”
Section: Current Technologiesmentioning
confidence: 99%